Advanced engineering analysis: the calculus of variations and functional analysis with applications in mechanics - Lebedev, L. P.; Cloud, Michael J.; Eremeyev, Victor A. (Singapore : World Scientific Pub. Co., 2012)
Advanced Engineering Analysis is a textbook on modern engineering analysis, covering the calculus of variations, functional analysis, control theory, as well as applications of these disciplines to mechanics. The book offers a brief and concise, yet complete explanation of essential theory and applications. It contains exercises with hints and solutions, ideal for self-study.
Includes bibliographical references and index.
Keywords: Engineering mathematics; Calculus; Mechanics; Electronic books